ETIKA KOMUNIKASI JUAL BELI BARANG DI MEDIA ONLINE BAGI MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI UIN SUMATERA UTARA - Gita Aulia Nurani, Abdul Rasyid, Ahmed Fernanda Desky (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
ABSTRACT: Communication ethics is currently often underestimated by many people, especially in online media communicators and communicants do not meet each other directly. This can be a concern for people, especially the ethics of buying and selling communication in online media. Knowing and implementing the existing rules correctly, it is very possible if various obstacles to shopping in online media can be overcome. For this reason, this study discusses whether the ethics of buying and selling communication in online media can affect consumers, as well as what obstacles are in the ethics of buying and selling communication in online media. Some important points in the ethics of communicating buying and selling in online media include creating existing moral values, creating honesty in every human being, the public has the right to as much information as possible regarding the reliability of the source, then do not provide information if it is known that it is inaccurate, and create a harmonious relationship. This study uses a descriptive qualitative research method where the researcher must describe the results of each finding. The number of informants is 10 people consisting of 5 people as online sellers and 5 people as online consumers. The research technique uses interviews, observation and documentation. Seeing from the number of people who use this online media to make buying and selling transactions, it is necessary to encourage all levels of society to have ethics on how to communicate well in online media.